Characterization of gut microbiota in adults with coronary atherosclerosis - Yu Dong; Rui Xu; Xiaowei Chen; Chuanli Yang; Fei Jiang; Yan Shen; Qiong Li; Fujin Fang; Yongjun Li; Xiaobing Shen (PeerJ, 2023)
Background Cardiovascular disease, which is mainly caused by coronary atherosclerosis, is one of the leading causes of death and disability worldwide. Gut microbiota likely play an important role in coronary atherosclerosis. This study aims to investigate the microbiota profile of adults with coronary atherosclerosis to provide a theoretical basis for future research. Methods Fecal samples were collected from 35 adult patients diagnosed with coronary atherosclerosis and 32 healthy adults in Nanjing, China, and the V3-V4 region of 16S rDNA genes was sequenced using high-throughput sequencing. Differences in alpha diversity, beta diversity, and gut microbiota composition between the two groups were then compared. Results A beta diversity analysis revealed significant differences between adults with coronary atherosclerosis and controls, but there was no statistical difference in alpha diversity between the two groups. There were also differences in the composition of the gut microbiota between the two groups. The genera, Megamonas, Streptococcus, Veillonella, Ruminococcus_torques_group, Prevotella_2, Tyzzerella_4, were identified as potential biomarkers for coronary atherosclerosis. Conclusion There are some differences in the gut microbiota of adults with coronary atherosclerosis compared to healthy adults. The insights from this study could be used to explore microbiome-based mechanisms for coronary atherosclerosis.